2013
DOI: 10.1155/2013/480713
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Inhibits ALDH Activity, Resistance to Oxidative Stress, and Metastatic Potential in Murine Osteosarcoma Cells

Abstract: Osteosarcoma (OS) is the most common primary malignancy of bone. Mortality is determined by the presence of metastatic disease, but little is known regarding the biochemical events that drive metastases. Two murine OS cell lines, K7M2 and K12, are related but differ significantly in their metastatic potentials: K7M2 is highly metastatic whereas K12 displays much less metastatic potential. Using this experimental system, the mammalian target of rapamycin (mTOR) pathway has been implicated in OS metastasis. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…Our previous study has demonstrated strong oxidative stress resistance of K7M2 cells [31]. PI staining of K7M2 cells incubated with hydrogen peroxide (H 2 O 2 ) displayed significantly increased percentages of apoptotic cells (PI-positive) in K7M2 cells after 2 days of CEE treatment compared with cells without CEE treatment (Fig.…”
Section: Chick Embryo Extract Decreases the Oxidative Stress Resistanmentioning
confidence: 86%
See 1 more Smart Citation
“…Our previous study has demonstrated strong oxidative stress resistance of K7M2 cells [31]. PI staining of K7M2 cells incubated with hydrogen peroxide (H 2 O 2 ) displayed significantly increased percentages of apoptotic cells (PI-positive) in K7M2 cells after 2 days of CEE treatment compared with cells without CEE treatment (Fig.…”
Section: Chick Embryo Extract Decreases the Oxidative Stress Resistanmentioning
confidence: 86%
“…P53 is also involved in osteosarcoma tumorigenesis [12,18], and epigenetic alterations of this gene contribute to the pathogenesis of osteosarcoma [35]. E-cadherin performs a key role in cell adhesion, and loss of E-cadherin is known as a key step leading to tumor metastasis [3,31,32]. Negative expression of E-cadherin was found to be correlated with higher metastasis and a shorter overall survival in human patients with osteosarcoma [24].…”
Section: Discussionmentioning
confidence: 99%
“…CSCs have protection mechanisms against oxidative stress, which can cause a resistance to cancer therapy. Studies have found that K7M2 cells, a high-ALDH-activity osteosarcoma (OS) cell line, have the ability of resist oxidative stress and invasive and oncogenic factor expression when compared with K12 cells (Mu et al, 2013). Thus, ALDH activity in cancer cells can neutralize oxidative stress and provide resistance to chemo-or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted inhibition of the signaling pathway of mTOR has been shown to reduce metastatic behavior in a mouse model of osteosarcoma [79] as well as human xenograft models [80]. Current and future clinical trials using mTOR inhibitors may prove therapeutically fruitful in the treatment of osteosarcoma [81].…”
Section: Mammalian Target Of Rapamycin (Mtor)mentioning
confidence: 99%